IMPROVING THE READING COMPREHENSION SKILLS OF PAI STUDENTS THROUGH QUESTION-ANSWER RELATIONSHIP (QAR) STRATEGY - Syamsul Rizal (Tarbawi, 2016)
This paper discusses the use of Question-Answer Relationship to improve the first semester of PAI students of IAIH NW Pancor. This study was conducted to overcome the students’ difficulties in reading comprehension and encourage the students to actively participate in the teaching-learning process through Question-Answer Relationship. The study was designed for collaborative classroom action research. The finding of the research that were conducted in two cycles showed that QAR strategy was worthy to improve the students’ reading skills and activate the students to participate in the teaching-learning process of reading. The students’ average score developed significantly from 59.00 in the pretest to 71.33(equal to 20.89%) in the first cycle. It developed to 74.33 (equal to 25.98%) in the second cycle in the scale of 0 – 100. Moreover, the findings of the study also described that this strategy improved the students’ participation. The students’ participation was 88.10% (equal to very good) in the first cycle and 88.39% (equal to very good) in the second cycle.